Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Polar Regions in the Anthropocene - Summerhayes, Colin; Zalasiewicz, Jan; Vidas, Davor; Williams, Mark (Research handbook on polar law, 2020)
Keywords: Antarktis; geologi; havrett; internasjonal; polarområdene

The Norwegian-British-Swedish Antarctic Expedition. Science and politics - Domaas, Christel Misund; Drivenes, Einar-Arne; Bones, Stian (UiT Norges arktiske universitet, 2019)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; historie; internasjonal; klimaendringer; politikk; samarbeid; vitenskap

Alien invasions in Antarctica - is anyone liable? - Hughes, Kevin A; Convey, Peter (Polar Research, 2014)
The introduction of non-native species to Antarctica in association with human activities is a major threat to indigenous biodiversity and the region's unique ecosystems, as has been well-demonstrated in other ecosystems globally. Existing legislation contained in the Protocol on Environmental Protection to the Antarctic Treaty does not specifically make the eradication of non-native species mandatory, although it is implicit that human-assisted introductions should not take place. Furthermore, to date, eradications of non-native species in the Treaty area have been infrequent and slow to progress. In 2005 an additional Annex (VI) to the Protocol was agreed concerning “Liability arising from environmental emergencies.” This annex focusses on prevention of environmental emergencies, contingency planning and reclaiming costs incurred when responding to an environmental emergency caused by another operator within the Antarctic Treaty area. However, the types of environmental emergencies covered by the annex are not defined. In this paper we highlight potential difficulties with the application of Annex VI in the context of non-native species control and eradication, including, for example, whether a non-native species introduction would be classified as an “environmental emergency” and therefore be considered under the terms of the annex. Even if this were the case, we conclude that the slow pace of approval of the annex by Antarctic Treaty Parties may prevent it coming into force for many years and, once in force, in its current form it is unlikely to be useful for reclaiming costs associated with the eradication or management of a non-native species.
Keywords: Antarktis; biodiversitet; internasjonal; miljøvern; politikk; samarbeid; økosystemer

Reading and thinking about International Polar Years: five recent books - Carlson, Dave (Polar Research, 2013)
Within the polar science community the Polar (and Geophysical) Years represent signal events. We often read, largely within geoscience literature, that those events represented positive and dramatic steps forward in international science. From five recent books - two historical compilations and three personal narratives - augmented by interviews with a few key participants, a more cautious picture emerges, of remarkable successes but also of occasional or even persistent missteps and deficiencies. An improved understanding of the IPY concept and experience can provide useful guidance for future polar and global science. Keywords: International Polar Year; International Geophysical Year; international science; history of polar science.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; bokanmeldelser; internasjonal; politikk; samarbeid; vitenskap

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

Continental shelf submission of Norway : in respect of Bouvetøya and Dronning Maud Land : executive summary (Oljedirektoratet, 2009)
Keywords: Bouvetøya; Dronning Maud Land; internasjonal; jus; kontinentalsokkel; politikk

Etableringen av Norsk polarinstitutt i 1948 : gammel vin i nye skinnsekker? - Nilsen, Frode (Universitetet i Tromsø, 2000)
Keywords: Antarktis; Norsk Polarinstitutt; historie; internasjonal; polarområdene; politikk